Effect of Epigallocatechin Gallate on the Inflammatory Response in Mice (Mus musculus) Kidneys - Gegana Wimaldy Airlangga; Balqis Aina Fajriya; Andreas Bandang Hardian (Universitas Airlangga, 2024)
Background: Epigallocatechin gallate is the primary polyphenol constituent of green tea. It has the ability to inhibit the pathological processes caused by oxidants. However, in certain cases, the green tea diet is known to exert pro-oxidant effects. In addition, studies have shown that epigallocatechin gallate negatively affects cells. Several studies on epigallocatechin gallate showed increased oxidative stress and decreased intracellular antioxidants. Furthermore, it can stimulate an inflammatory response from the innate immune system, which may contribute to the elimination of the effects of epigallocatechin gallate. Purpose: This study aims to investigate the inflammatory responses (IL-1, IL-6, and TNF-α) in mice kidneys due to epigallocatechin gallate. Methods: This study involved the use of experimental animals aged between two and three months with an average body weight of 20 grams. The animals were randomly divided into two groups, namely the control group and the epigallocatechin gallate treatment group, with each group consisting of 16 samples. The dose of epigallocatechin gallate used in this study was 750 mg/kg bw. The treatment was administered for three days, after which the kidneys were collected. Immunohistochemical staining was used to observe the inflammatory response, including IL-1, IL-6 and TNF-α. Subsequently, all the data were collected and statistically analyzed using an independent t-test. Results: The results of the data analysis showed a significant difference in the expression of IL-6 (p = 0.018) and TNF-α (p = 0.000), but no significant difference in the expression of IL-1 (p = 0.106). Conclusion: In conclusion, epigallocatechin gallate was found to induce an inflammatory response in mice kidneys.